Development of novel rectangular photomultiplier tubes for gamma-ray spectroscopy - Beavers, Jace (Kansas State University, 2024)
Through the development of phenomenological, stochastic electron-emission models coupled to finite-element multiphysics simulations, two novel rectangular-window photomultiplier tubes (PMTs) for use in gamma-spectroscopy applications have been designed, and various ultra-high vacuum (UHV) fabrication techniques have been explored. The geometries of commercially-produced scintillation spectrometers have historically been driven by standard circular-window PMTs with a maximum diameter of 127 mm, limiting the absolute efficiency and mobility of such devices. There exists a need for rectangular scintillation spectrometers having a large frontal-area and reduced thickness to support discreet, highefficiency detection and analysis of radioactive materials. Compact, rectangular PMTs and solid-state detectors may be tiled to achieve fine-resolution spectroscopy on such scales. However, increased cost, complexity, and power consumption have limited their implementation in mobile detection applications. Large-area rectangular PMTs circumvent many of these issues, while simultaneously improving photon collection and spectrometer resolution. To support coupled gamma-ray/optical photon transport simulations used for the development of novel scintillation spectrometers, experiments exploring PMT anode response and the various sources of spectrometer resolution were performed using an ET Enterprises 9490B PMT as a test article. Spatially-dependent relative anode response measurements were taken to understand how response non-uniformity affects spectrometer resolution. Collimated 137Cs gamma-ray beam measurements were used to investigate the spatial dependence of scintillator response for unique crystal geometries. These results will be used to inform and validate Monte Carlo simulations in the future. Stochastic models of photoelectron emission from the photocathode and secondary electron emission from the dynodes were implemented in COMSOL Multiphysics finite-element simulation software to enable novel PMT design investigations. Coupled electrostatic and electron-transport simulations were validated using the well-quantified performance of an ET Enterprises 9214B PMT. This methodology was then carried over to an iterative design process to develop and predict the single and multi-photoelectron response of novel PMTs with reflective and transmissive photocathodes. Finally, several vacuum fabrication techniques were investigated to explore novel PMT fabrication and are discussed herein. A metal vacuum envelope was produced through traditional machining and polishing processes, while additional components were added via laser welding. Two approaches to compact multiplier structure fabrication were investigated. Glass-glass and glass-metal UHV sealing methods are described and testing was performed on borosilicate samples. Finally, a UHV physical vapor deposition and assembly system was constructed for sensitive thin film growth and PMT fabrication. The initial characterization of this system and thin film growth efforts are described. Alternative fabrication methods are also discussed.
Keywords: Photomultiplier tube; Scintillation spectrometer; Gamma-ray spectroscopy; Multiphysics simulation; Ultra high vacuum